All part of the process? A qualitative examination of change in online child pornography behaviors. Issue 3 (3rd July 2018) - Steely, Mollee; Ten Bensel, Tusty; Bratton, Tabrina; Lytle, Robert
ABSTRACT: Over the past two decades, there has been increased attention on offending behaviors and motivations of child pornography offenders (CPOs). Although existing research has provided a knowledgeable foundation in regard to this offending subpopulation, the literature has been relatively limited on examining changes in offender behaviors and motivations. This study used interviews with 25 online CPOs in a southern state to identify themes underlying offending behaviors and motives at onset, as well as, continuation of offending over time. We found that offenders reported various circumstances (ranging from intentional to unintentional) and motivations (including thrill-seeking and attraction) at onset; however, CPOs reported thrill-seeking and attraction to be the most common factors driving their continued offending. We applied these themes to the existing literature on child pornography offending and recommended directions for future research. Based on our findings, we offered considerations for the treatment of CPOs.